Critically Ill Patient with Acute Exacerbation of Chronic Obstructive Pulmonary Disease Developing Sepsis and Potassium Disorder: a Case Report in Secondary Hospital Setting - Regia Anadhia Pinastika; Indah Rahmawati; Tiara Nadya Putrianda (Jurnal Profesi Medika : Jurnal Kedokteran dan Kesehatan, 2022)
Sepsis and electrolyte disturbances are frequently experienced among acute exacerbation of chronic obstructive pulmonary disease (AECOPD) patients. It is characterized by organ failure brought on by unbalanced host response to infection. A 63-year-old male presented to the hospital with the complaint of breathlessness with the oxygen saturation of 76%. The leukocyte level increased to 19.000 and the Potassium level decreased to 2.88. The combination of antibiotics, Potassium supplement, oxygen support through NRM of 15 liters per minute and symptomatic treatment were administered to the patient. The NRM was then changed to HFNC due to his worsening condition and successfully decreased oxygen demand. The patient’s condition has made a significant improvement after seven days of hospitalization. Patients with AECOPD are at higher risk of developing sepsis and electrolyte disturbances. Sepsis will change the biological system of the body due to different pathophysiology such as electrolyte imbalance and obviously engaged with the pathogenesis of ensuing regular intensifications. It is important for the clinicians to know the effective management for the patient, so that the critical phase can be passed even at the limited facilities.